Economic complexity and environmental pollution: evidence from the former socialist transition countries - Bucher, Florian; Scheu, Lucas; Schröpf, Benedikt (Empirica, 2023)
This study examines the link between economic complexity and environmental pollution by exploiting a massive and unprecedented decline of CO2 emissions and complexity in the former socialist transition countries after the fall of the iron curtain. We refer to the extended theories of the Environmental Kuznets Curve (EKC), stating that environmental pollution follows an inverted u-shaped course with respect to economic complexity. Using comprehensive data of 27 countries for the period 1995-2017, our results show that the EKC can be found for countries whose complexity rose over time. Additionally, since the results for production-based and consumption-based CO2 emissions are similar, we can discard emissions offshoring as a major explaining factor. Consequently, our findings suggest that more complex products have influenced the u-shaped course of the EKC. However, as the turning point is associated with high levels of pollution, our estimates imply that complexity may even exacerbate environmental issues in the short and middle run in less developed countries.
CRIS-Team WoS Importer:2023-05-26

The dynamics of wage dispersion between firms: the role of firm entry and exit - Schröpf, Benedikt (Journal for Labour Market Research, 2023)
Although wage inequality is an important and widely studied issue, the literature is vastly silent on the relationship between firm entry and exit and the wage dispersion between firms. Using a 50% random administrative sample of West German establishments over the period 1976–2017, I study wage dispersion dynamics between and within the groups of entering, exiting, and incumbent establishments by examining the distribution of average wages across establishments. The results show that entering establishments became increasingly unequal over time, thereby contributing to the rise in wage dispersion between establishments. However, exit rates of young and low-wage establishments have dampened this effect. These findings suggest considering the consequences for wage inequality when designing and assessing policy instruments for firm entry and exit.
CRIS-Team Scopus Importer:2023-01-13
Keywords: Firm dynamics; Firm entry; Firm exit; Germany; Wage dispersion